Perubahan Kebijakan Publik Akibat Media Framing Pemberitaan Rencana Penghapusan Gas Tabung Elpiji - Setyaningtyas, Emilya; Sihombing, Aprida Mardelina; Anita Yunia (Jurnal Paradigma, 2026)
The 3-kilogram (kg) LPG cylinder is a primary energy source for low-income households and micro-enterprises in Indonesia. In February 2025, the government implemented a policy restricting the sale of subsidized 3 kg LPG exclusively through registered distribution bases, eliminating informal retailers. This policy immediately triggered widespread public reactions and intense national media coverage. This study aims to analyze how national online media framed the LPG distribution policy and how such framing contributed to public pressure that led to policy reconsideration. Using a qualitative approach and Entman’s framing analysis model, this study examines four framing elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were collected from news articles published by four major Indonesian online media outlets detik.com, kompas.com, republika.com, and liputan6.com during January–March 2025. The findings indicate that dominant media framing emphasized social injustice, limited accessibility, and weak policy communication, which amplified public dissatisfaction and accelerated government policy adjustment. This study contributes to media framing literature by demonstrating how media framing operates not only as a meaning-construction mechanism but also as a catalyst for short-term public policy change. The findings also highlight the strategic role of Government Public Relations (GPR) in managing policy communication for sensitive public issues.